Circulating MicroRNAs: Biogenesis and Clinical Significance in Acute Myocardial Infarction - Zhang, Lei; Ding, Han; Zhang, Yuan; Wang, Yin; Zhu, Wenjie; Li, Peifeng (Frontiers in Physiology, 2020)
Acute myocardial infarction (AMI) causes many deaths around the world. Early diagnosis can prevent the development of AMI and provide theoretical support for the subsequent treatment. miRNAs participate in the AMI pathological processes. We aim to determine the early diagnostic and the prognostic roles of circulating miRNAs in AMI in the existing studies and summarize all the data to provide a greater understanding of their utility for clinical application. We reviewed current knowledge focused on the AMI development and circulating miRNAs formation. Meanwhile, we collected and analyzed the potential roles of circulating miRNAs in AMI diagnosis, prognosis and therapeutic strategies. Additionally, we elaborated on the challenges and clinical perspectives of the application of circulating miRNAs in AMI diagnosis. Circulating miRNAs are stable in the circulation and have earlier increases of circulating levels than diagnostic golden criteria. In addition, they are tissue and disease-specific. All these characteristics indicate that circulating miRNAs are promising biomarkers for the early diagnosis of AMI. Although there are several limitations to be resolved before clinical use, the application of circulating miRNAs shows great potential in the early diagnosis and the prognosis of AMI.